Race/Ethnicity, Socioeconomic Characteristics, Coethnic Social Ties, and Health: Evidence From the National Jewish Population Survey - Pearson, Jay A. (American Public Health Association, 2011)
Objectives. We explored whether a White ethnic group with a history of structural disadvantage, Jewish Americans, shows evidence of continuing health impact independent of socioeconomic position (SEP), whether coethnic social ties appear health protective, and whether the strength of any protection varies by SEP. Methods. In a series of ordered logistic regressions, we analyzed data from the National Jewish Population Survey, 2000–2001, regressing self-rated health on race/ethnicity, education, and income for US Blacks, Jews, and other Whites and, for Jews alone, indicators of coethnic social ties. Results. controlling for SEP indicators, the self-rated health of Jews converged with that of Blacks and was significantly worse than that of other Whites. Access to coethnic social ties was associated with better self-rated health among Jews, with the strongest estimated association among those of lower SEP. Conclusions. The finding that a White ethnic group with a favorable socioeconomic profile reported significantly worse health than did other Whites, after controlling for SEP, calls for better understanding of the complex interplay of cultural, psychosocial, and socioeconomic resources in shaping population health.